Geographical Delimitation of a Mediterranean Territory with Cultural and Heritage Interest. - Sánchez-Sánchez, Miguel Ángel (Revista de Estudios Andaluces, 2018)
A better knowledge of the territory facilitates an adequate management of it. Some areas belonging to the Mediterranean area show great diversity (natural, human, cultural, etc.), complexity and fragile equilibria. Providing a geographical delimitation that facilitates the study of such issues, especially those with cultural and patrimonial interest. The delimitation of the Ricote Valley, in the Region of Murcia, can contribute to a better management of such complexities, fragilities and diversities. Being such a delimitation the objective of this investigation, which can serve for future delimitations of similar territories. The geographic information of interest, obtained from different sources, according to their presence and qualification in different catalogs, is analyzed and valued. Surveys are also conducted to residents and non-residents, reinforcing this research as a whole. This procedure allows to advance in the delimitation of singular territories with cultural and patrimonial interest.